"Get a £10 Free Bet Every Week!"—Gambling Advertising on Twitter: Volume, Content, Followers, Engagement, and Regulatory Compliance. Issue 4 (October 2021) - Rossi, Raffaello; Nairn, Agnes; Smith, Josh; Inskip, Christopher
The internet raises substantial challenges for policy makers in regulating gambling harm. The proliferation of gambling advertising on Twitter is one such challenge. However, the sheer scale renders it extremely difficult to investigate using conventional techniques. In this article, the authors present three U.K. Twitter gambling advertising studies using both big data analytics and manual content analysis to explore the volume and content of gambling ads, the age and engagement of followers, and compliance with U.K. advertising regulations. They analyze 890, 000 organic ads from 417 accounts along with data on 620, 000 followers and 457, 000 engagements (replies and retweets). They find that approximately 41, 000 U.K. children follow Twitter gambling accounts, and that two-thirds of gambling advertising tweets fail to fully comply with regulations. Ads for e-sports gambling are markedly different from those for traditional gambling (such as on soccer, casinos, and lotteries) and appear to have strong appeal for children, with 28% of engagements with e-sports gambling ads coming from users under 16 years old. The authors make six policy recommendations: spotlight e-sports gambling advertising, create new social media–specific regulations, revise regulation on content appealing to children, use technology to block users under 18 years from seeing gambling ads, require ad labeling of organic gambling tweets, and deploy better enforcement.